2005
DOI: 10.1128/iai.73.12.7996-8001.2005
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Leishmania donovani Infection Promotes Bystander CD8 + -T-Cell Expansion and Heterologous Immunity

Abstract: It has been proposed that long-lived memory T cells generated by vaccination or infection reside within a memory compartment that has a finite size. Consequently, in a variety of acute infection models interclonal competition has been shown to lead to attrition of preexisting memory CD8 ؉ T cells. Contrary to expectations, therefore, we found that chronic Leishmania donovani infection of Listeria-immune mice results in heightened protection against subsequent Listeria challenge. This protection was associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…One theory is that bystander activation following infection might simply be a homeostatically induced proliferation following the T-cell depletion characteristic of some infections. Alternatively, infection could induce splenomegaly, creating more space for heterologous memory cells [15]. Indeed some of the characteristics seem similar, yet the experiments of Gilbertson et al [16], performed in mice infected with Mycobacterium avium (which naturally induces T-cell depletion), indicate that bystander activation and homeostatic proliferation are similar but distinct processes.…”
Section: Defining Bystander T-cell Activationmentioning
confidence: 97%
“…One theory is that bystander activation following infection might simply be a homeostatically induced proliferation following the T-cell depletion characteristic of some infections. Alternatively, infection could induce splenomegaly, creating more space for heterologous memory cells [15]. Indeed some of the characteristics seem similar, yet the experiments of Gilbertson et al [16], performed in mice infected with Mycobacterium avium (which naturally induces T-cell depletion), indicate that bystander activation and homeostatic proliferation are similar but distinct processes.…”
Section: Defining Bystander T-cell Activationmentioning
confidence: 97%
“…There is always a question of how much of heterologous immunity is mediated exclusively by cross‐reactive mechanisms and how much by non‐specific bystander mechanisms, and this remains an issue even when cross‐reactive epitopes can be found (). Several studies have concluded that memory T cells can be subjected to bystander activation by cytokines independent of TCR signaling and that these non‐specifically activated cells may contribute to heterologous immunity (15, 102–104). It has also been reported that IL‐12 and IL‐18 can non‐specifically stimulate the production of IFNγ by memory T cells (16), and VV infection will induce the synthesis of IL‐12 in mice (6).…”
Section: Mouse Models Of Heterologous Immunity With Defined T‐cell Crmentioning
confidence: 99%
“…GB virus C can inhibit HIV replication and HIV-infected individuals that are co-infected with GB virus C have an almost four-fold reduced rate of mortality (Xiang et al, 2001). Similarly, mice chronically infected with the protozoan parasite Leishmania were protected against subsequent bacterial challenge, potentially due to the induced splenomegaly and expansion of CD8 T cells (Polley et al, 2005). …”
Section: Persisting Infections Benefiting the Hostmentioning
confidence: 99%